TRADISI UPAH-UPAH MASYARAKAT MELAYU DESA SUNGAI SIALANG KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR - Sukasni Sukasni '; Ridwan Melay Ridwan Melay; Marwoto Saiman Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Tradition is custom made by a group of people that are passed from generation to generation captivate the generations that and still performed today. Tradition can not be separated from the culture, because the value of the cultural value system is the highest level and the most abstract of customs. Tradition upah-upah is a tradition that is carried by the community Malay Sungai sialang subdistrict Batu Hampar Rokan Hilir, the tradition is carried out to restore the spirit of someone who lost caused by several things such as to avoid a disaster, take new life and when it is reached ideals. The purpose of this study was to determine the tradition of upah-upah for people Malay Sungai Sialang subdistrict Batu Hampar Rokan Hilir, to know the process of implementation of the tradition of upah-upah Malay community Sungai sialang subdistrict Batu Hampar Rokan Hilir, to determine the function of the tradition of upah-upah for the Malay community Sungai Sialang subdistrict Batu Hampar Rokan Hilir. The method used in this research is descriptive qualitative. Data were obtained from interviews and then analyzed by the language itself. The research site is the village of Sungai Sialang subdistrict Batu Hampar Rokan Hilir. When the study started from a seminar proposal to the thesis examination. Data collection techniques used are observation, documentation techniques, interview techniques and technical literature. The results showed that the wages tradition still carried out today by the Malay community Sungai Sialang Village. Tradition upah-upah implemented in order to restore the spirit of someone who threatened his life, encouragement and confidence and grateful on a success. Upah-upah tradition has two functions, functions for the individual and for society functions Melay Sungai Sialang.Keywords: Tradition, Upah-upah, Rokan Hilir